2020
DOI: 10.1186/s40008-020-00195-4
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of entrepreneurship education in shaping entrepreneurial intentions

Abstract: Few studies investigated the role of entrepreneurship education in students’ entrepreneurial intentions. These studies produced controversial results which invited the attention of researchers for further investigations. This paper examines the moderating role of entrepreneurship education on the predictive value of attitude, subjective norms and self-efficacy for entrepreneurial intentions. True Experimental Design (post-test-only control group design) is used to investigate the change in the nature and magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
121
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(180 citation statements)
references
References 38 publications
22
121
2
5
Order By: Relevance
“…Therefore, through entrepreneurship education, graduates were able to search for and seize business opportunities (Densberger, 2014). This finding is similar to Ndofirepi (2020) and Shah et al (2020), that attitudes towards entrepreneurship, proactiveness, riskpropensity and self-efficacy were significant factors in influencing entrepreneurial intentions among graduates. The results also confirmed the associations premised on the theory of planned behaviour (TPB) (Abdullah et al, 2017); which states that through the influence of personality traits, the attitude changes which impacts on the behaviour or intention to start business.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Therefore, through entrepreneurship education, graduates were able to search for and seize business opportunities (Densberger, 2014). This finding is similar to Ndofirepi (2020) and Shah et al (2020), that attitudes towards entrepreneurship, proactiveness, riskpropensity and self-efficacy were significant factors in influencing entrepreneurial intentions among graduates. The results also confirmed the associations premised on the theory of planned behaviour (TPB) (Abdullah et al, 2017); which states that through the influence of personality traits, the attitude changes which impacts on the behaviour or intention to start business.…”
Section: Resultssupporting
confidence: 80%
“…Thus, for university graduates to have a positive attitude towards entrepreneurship as a career option, they need to be empowered through entrepreneurship education. This is similar to that of Shah et al (2020), who found out that attitude towards entrepreneurship moderated the relationship between personal attributes of students and intention to start business.…”
Section: Mediating Role Of Attitude Towards Impact Of Entrepreneurshipsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, it is imperative to investigate the conditional effects of gender, major, and educational experiences to separate out the unique contribution of each variable [90,91] on the entrepreneurship mindsets. Based on a great deal of evidences for the effect of entrepreneurship education on entrepreneurial attitude [78,[92][93][94], intention [36,78,[95][96][97], and behavior [98][99][100][101], we believe that the educational experiences in entrepreneurship would play the most crucial role in the college students' entrepreneurial mindset even after controlling for the effects of gender and major.…”
Section: Hypothesis 4e (H4e)mentioning
confidence: 99%